2013
DOI: 10.1080/02701367.2013.839025
|View full text |Cite
|
Sign up to set email alerts
|

Positive Youth Development: Minority Male Participation in a Sport-Based Afterschool Program in an Urban Environment

Abstract: By promoting positive relationships and providing opportunities for self-exploration in a safe and trusting environment, afterschool programs can cultivate positive youth development in minority boys, at least in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 15 publications
2
52
0
3
Order By: Relevance
“…First, the program appeared to have appeal because of the use sport as a medium, the provision of a caring relationship for youths, and the expectation of positive synergy between sport and life skills development. The findings of this study confirm the contention of the literature that sport is a strong hook to attract youth and a viable context and tool for youth development programs (Fuller et al, 2013;Lee & Martinek, 2009). In addition, the parents expected the sports program to close the guidance gap (Hellison, 1985) by providing structured mentoring for their children who lacked sufficient guidance.…”
Section: Discussionsupporting
confidence: 81%
“…First, the program appeared to have appeal because of the use sport as a medium, the provision of a caring relationship for youths, and the expectation of positive synergy between sport and life skills development. The findings of this study confirm the contention of the literature that sport is a strong hook to attract youth and a viable context and tool for youth development programs (Fuller et al, 2013;Lee & Martinek, 2009). In addition, the parents expected the sports program to close the guidance gap (Hellison, 1985) by providing structured mentoring for their children who lacked sufficient guidance.…”
Section: Discussionsupporting
confidence: 81%
“…Armour and Sandford (2013) did not provide an explanation for the improvement in empathy. Two social interaction skills (i.e., communications skills [Armour & Sandford, 2013;Fuller et al, 2013;Riley & Anderson-Butcher, 2012] and conflict resolution skills [E. Fuller et al, 2013;Riley & Anderson-Butcher, 2012]) were reported as improving. An interesting observation is that the four studies that reported improvements in social interaction skills were qualitative studies.…”
Section: Social Life Skillsmentioning
confidence: 99%
“…For instance, one program included competitive sports activities at a community sports club (E. , whereas another program was a sportsbased summer camp in which program staff tried to create a mastery-oriented environment (Ullrich-French et al, 2012). Four of the programs in which participants were reported as developing self-regulation skills were based on PYD principles (E. Fuller et al, 2013;Riley & Anderson-Butcher, 2012;Walsh, Ozaeta, & Wright, 2010). One example of a PYD-based sports program that strengthened the development of self-regulation (i.e., self-efficacy, self-concept, and resistance skills) was a program that tried to create a supportive and empowering environment (Fuller et al, 2013).…”
Section: Cognitive Life Skillsmentioning
confidence: 99%
See 2 more Smart Citations